INCREASING HYDROPONIC PLANT CULTIVATION WITH SMART RESOURCE CONTROLLING - Fauziah Hanum Simbolon; Siti Anisah; Solly Aryza (Sean Institute, 2023)
Hydroponics is a form of cultivating plants without using soil which is starting to be popular among the general public. Hydroponics has several circulation systems such as NFT and DFT. Apart from that, hydroponics also has disadvantages, especially in terms of circulating nutrient fluids and using pumps. Farmers tend to circulate nutrient fluid using a pump that is continuously on for 24 hours, where the power used is power supplied from PLN. Apart from that, the pump is also continuously on for 24 hours, which can result in the pump's lifespan being shorter. The designed hydroponics can be used with an NFT or DFT system which is equipped with a water level sensor and a DS18B20 sensor which can measure the volume of nutrient fluid and also measure the temperature of the nutrient fluid in the hydroponic pipe. The pump comes from solar heat produced from solar panels. Here the water level sensor, relay, and assisted by the water flow sensor and DS18B20 sensor as the main key in the nutrient fluid circulation process in hydroponic plants are assisted by a 12V DC pump, and all of this does not escape the control system used to control the performance of the sensor, namely the system Arduino microcontroller.